Retreatment with bendamustine-containing regimens in patients with relapsed/refractory chronic lymphocytic leukemia and indolent B-cell lymphomas achieves high response rates and some long lasting remissions. Issue 8 (August 2013) - Weide, Rudolf; Feiten, Stefan; Friesenhahn, Vera; Heymanns, Jochen; Kleboth, Kristina; Thomalla, Jörg; van Roye, Christoph; Köppler, Hubert
Abstract Bendamustine and bendamustine/rituximab combinations have shown high efficacy in relapsed/refractory chronic lymphocytic leukemia (CLL) and indolent B-cell malignancies (non-Hodgkin lymphoma, NHL). No data exist about bendamustine retreatment after relapse, concerning efficacy and toxicity in this patient population. Eighty-eight outpatients (57 patients with CLL, 31 patients with NHL) who had previously been treated with bendamustine were retreated with a bendamustine regimen. Treatment consisted of bendamustine (B) or bendamustine + mitoxantrone (BM) or bendamustine + rituximab (BR) or bendamustine + mitoxantrone + rituximab (BMR). Median age was 72 years (50–88). A reversible grade 3 or 4 leukocytopenia or thrombocytopenia was observed in 24% and 13%, respectively. The overall response rate (ORR) was 76% (7% complete remission [CR], 69% partial remission [PR]) with 77% (6% CR, 71% PR) in CLL and 71% (8% CR, 63% PR) in NHL. ORR according to regimen was as follows: B: 57% (14% CR, 43% PR), BM: 70% (4% CR, 66% PR), BR: 55% (10% CR, 45% PR), BMR: 84% (7% CR, 78% PR). Bendamustine retreatment is feasible and achieves high response rates and some long lasting remissions.